Microglial polarization in TBI: Signaling pathways and influencing pharmaceuticals - Li, Yun-Fei; Ren, Xu; Zhang, Liang; Wang, Yu-Hai; Chen, Tao (Frontiers in Aging Neuroscience, 2022)
Traumatic brain injury (TBI) is a serious disease that threatens life and health of people. It poses a great economic burden on the healthcare system. Thus, seeking effective therapy to cure a patient with TBI is a matter of great urgency. Microglia are macrophages in the central nervous system (CNS) and play an important role in neuroinflammation. When TBI occurs, the human body environment changes dramatically and microglia polarize to one of two different phenotypes: M1 and M2. M1 microglia play a role in promoting the development of inflammation, while M2 microglia play a role in inhibiting inflammation. How to regulate the polarization direction of microglia is of great significance for the treatment of patients with TBI. The polarization of microglia involves many cellular signal transduction pathways, such as the TLR-4/NF-κB, JAK/STAT, HMGB1, MAPK, and PPAR-γ pathways. These provide a theoretical basis for us to seek therapeutic drugs for the patient with TBI. There are several drugs that target these pathways, including fingolimod, minocycline, Tak-242 and erythropoietin (EPO), and CSF-1. In this study, we will review signaling pathways involved in microglial polarization and medications that influence this process.